PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V UPTD SD NEGERI 88 PAREPARE - Yusuf Yusuf (PINISI :Journal of Teacher Professional, 2020)
This research is motivated by the low learning outcomes of students in the fifth grade elementary school mathematics. This study aims to improve the learning outcomes of mathematics in the learning material of the smallest common multiples through the Problem Based Learning (PBL) model. The subjects of this study were class V students, totaling 16 students, consisting of 10 boys and 6 girls. This study uses a classroom action research design. This research was conducted in two cycles. Each cycle was carried out in two meetings with a time of 2 x 35 minutes. Instruments to collect data are test and non-test. The results showed that the steps for implementing the Problem Based Learning (PBL) model were: (1) orienting the problem, (2) organizing students to learn, (3) guiding students (individuals and groups) to conduct investigations, (4) presenting the results. or discussion, (5) analyze and evaluate problem solving. Based on observations of the learning process both in cycle I and in cycle II, the data shows that students' mathematics learning outcomes in the material of the smallest common multiples increase. The percentage in the first cycle is 43.75% who get sufficient criteria and in the second cycle is 86.36% who get very good criteria. The percentage of student learning outcomes has reached the predetermined success indicators, namely 80%. This leads to the conclusion that the application of the problem-based learning model (PBL) is able to improve mathematics learning outcomes in the learning material of the smallest common multiple of fifth grade elementary school.